Who will excel in advanced endoscopy? A study assessing the criteria and perceptions of experts with regard to selection of ERCP and EUS trainees - Campos, Sara; Devière, Jacques; Arvanitakis, Marianna (Endoscopy International Open, 2023)
Background and study aims Training program directors (TPDs) and experts play a crucial role in selecting ERCP/EUS trainees and determining the workforce in endoscopy. Additionally, prospective trainees should know what TPDs/experts expect from them. Nonetheless, the criteria and perceptions used in this selection have not been clarified. The aim of this study was to identify TPD/expert values/beliefs regarding personal attributes needed for selecting trainees that can excel and those which may lead to disqualification; compare perspectives between TPDs/experts and trainees regarding the selection process and critical trainee characteristics; and investigate the general approach and satisfaction regarding current application process for ERCP/EUS training.Methods We conducted a web-based survey to collect general opinion and data regarding the application process and trainee selection and disqualification from training. European TPDs/experts and trainees were invited to participate.Results Thirty-six TPDs/experts and 25 trainees from 18 countries responded. The application process is mainly driven by individual request (86.1 %). Almost half of TPDs/experts felt only moderately (38.9 %) to slightly (8.3 %) satisfied with the current application process. TPDs/experts value a diversity of trainee characteristics, but mainly traits such as “honesty,” “being a team player,” and “self-awareness” (72.2 % each). Technical skills ranked seventh as considered “extremely important.” “Disregard for patient welfare” and “lack of work ethic” were the most common reasons for disqualification. TPDs/experts and trainees agreed in most questions.Conclusions This survey outlines trainee selection criteria for ERCP/EUS training. Non-technical skills are the most valued by TPDs/experts. While knowledge and technical expertise are clearly important, understanding that professional attitudes are highly regarded may help direct the application process more effectively.